The misperception of inflation by Irish consumers - David Duffy; Pete Lunn (The Economic and Social Research Institute (ESRI), 2008)
How people perceive and forecast inflation has the potential to impact on a range of economic outcomes. We reveal large, systematic overestimation of inflation by Irish consumers, which varies by social group. In contrast to previous work in this area, our models suggest the upward bias and the variation by social group should be considered substantially separate phenomena. We also offer evidence that inflation misperceptions are linked to attitudes and intentions with respect to consumption and saving and, hence, are likely to affect household decision-making. The findings therefore raise issues regarding the relationship between financial literacy and consumer behaviour.
Keywords: 330; Inflationsrate; Inflationserwartung; Wahrnehmung; Soziale Gruppe; Konsumentenverhalten; Sparen; Irland